Mineralisation of target hydrocarbons in three contaminated soils from former refinery facilities - Towell, M. G.; Bellarby, J.; Paton, Graeme I.; Coulon, Frederic; Pollard, Simon J. T.; Semple, Kirk T. (Elsevier Science B.V., Amsterdam., 2011)
This study investigated the microbial degradation of 14C-labelled hexadecane, octacosane, phenanthrene and pyrene and considered how degradation might be optimised in three genuinely hydrocarbon contaminated soils from former petroleum refinery sites. Hydrocarbon mineralisation by the indigenous microbial community was monitored over 23 d. Hydrocarbon mineralisation enhancement by nutrient amendment (biostimulation), hydrocarbon degrader addition (bioaugmentation) and combined nutrient and degrader amendment, was also explored. The ability of indigenous soil microflora to mineralise 14C-target hydrocarbons was appreciable; ≥ 16% mineralised in all soils. Generally, addition of nutrients or degraders increased the rates and extents of mineralisation of 14C-hydrocarbons. However, the addition of nutrients and degraders in combination had a negative effect upon 14C-octacosane mineralisation and resulted in lower extents of mineralisation in the three soils. In general, the rates and extents of mineralisation will be dependent upon treatment type, nature of the contamination and adaptation of the ingenious microbial communit